Peran Pendidikan dan Pelatihan Manajemen Keuangan dalam Meningkatkan Kapabilitas Karyawan Bank BCA Pematangsiantar - Zulia Almaida Siregar; Roger Susilo Napitupulu; Dimas Prayogi; P.A.M. Zidane R.W.P.P. Zer; Michael Kevin Artado Sihombing; Abdi Rahim Damanik (Departement of Mathematics Education, 2024)
This study aims to analyze the role of financial management education and training in enhancing the capabilities of employees at Bank BCA Pematangsiantar. Education and training are crucial components in human resource development, which not only increase knowledge and skills but also strengthen employees' competencies in managing complex financial tasks. This study employs a quantitative approach using a survey method to collect data from employees at Bank BCA Pematangsiantar. The data are analyzed using descriptive and inferential statistical techniques to measure the impact of education and training on employee capabilities.The results of the study show that financial management education and training programs have a significant impact on improving employee capabilities. Employees who participated in these programs demonstrated improvements in financial analysis, risk management, and better financial decision-making. Additionally, the training also enhanced employees' confidence in performing their daily tasks.This study concludes that investing in financial management education and training is an effective strategy to enhance employee capabilities and, ultimately, the overall performance of Bank BCA Pematangsiantar. Recommendations are given to the bank management to continue supporting and developing relevant education and training programs, as well as creating a work environment that fosters continuous learning.